Psychological intervention on canoeists in calm waters - Isorna Folgar, M.; Farina Rivera, F.; Alacid Carceles, F.; Vazquez Figueiredo, M. J. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
The personal characteristics of the athlete and, in particular, the search for talents, have formed part of many traditional research areas in sport. Although physical and physiological exceptionality have been the most studied aspects, lately the psychological characteristics have been analysed more and more frequently. The purpose of a highly competitive sport is to ensure that the athletes, within limits set by their own regulation of the practiced activity, yield their potential to the fullest in order to achieve maximum success. Mahamud, Tuero and Márquez (2005) argue that the ultimate goal of training in a competitive sport is to expand and fine-tune the physical, technical and tactical-strategic resources of athletes. Here, Buceta (1991) says these high performance athletes learn to improve their skills with techniques beyond regular training, in order to maximize their potential and performance during the competition. In competitive sport and athletic performance psychological variables of considerable importance are involved such as motivation, attention, stress, anxiety, self-confidence, mood, self-control and self-regulation, cohesion, interpersonal skills or emotional adjustment (Garcia Rodriguez, Andrade and Arce, 2006; Gil, Capafons and Labrador, 1993). Not surprisingly, the psychological training has slowly been gaining greater significance not only in enhancing positive athletes' behaviours but also in eliminating or controlling the negative ones. From the psychology of sports it is recognized and defended that coaches need to have psychological knowledge (Buceta, 1999; 2004); since the classical ordinary training does not always allow to increase the performance of elite athletes, especially when they have reached a high level of performance. In fact, Orlick and Partington (1988) believe that the integration of psychological, physical technical and tactical components, represents fifty percent of the effectiveness of the athlete's potential. Despite the influence that the psychological factors have on sports performance is amply demonstrated, there is still much research to be done about the degree of incidence or the impact they have on each sports discipline. Specifically, shaping the career of a canoeist require high personal psychological demands, given the nature of this sport, that are particularly necessary not only because of the high training load to which they are subjected, but also because of the external weather influences that are often unfavourable: training in open waters, cold weather, wind, rain, mists, etc., which requires a strong self-improvement, especially during the winter months (Lenz, 2008).